Implementing an Action Over Inertia Group Program in Community Residential Rehabilitation Services: Group Participant and Facilitator Perspectives - Rees, Erin F.; Ennals, Priscilla; Fossey, Ellie (Frontiers in Psychiatry, 2021)
Introduction: A time-use focused intervention, Action over Inertia (AOI) designed to address restricted activity patterns and support recovery, was adapted for use in Australian community residential mental health services. Method: Qualitative case study research explored the use of AOI groups across three Community Care Units from the perspectives of group participants with enduring mental illness and group facilitators. Fifteen interviews were conducted: five group participants were interviewed twice four weeks apart; and five group facilitators on completion of the group intervention. Interview data were analysed thematically using constant comparative and cross-case analytic methods. Findings: Two overarching themes, ‘Making Change’ and ‘Facilitating Change’ were identified. Efforts to make change in participants’ lives were supported by: recognising the value of personally meaningful activities for wellbeing and of activity experiences that fostered hope and recovery, whereas a sense of ‘stuckness’, time for activities and life events could disrupt ‘getting me going’. For the facilitators, facilitating change involved recognising inertia as a challenge; getting people going; and looking at how AOI intervention works to impact inertia. Conclusion: AOI in a group format supports participants to identify barriers to more active living; to appreciate how time-use and wellbeing interrelate; and to reframe and take steps to overcome inertia. Further research should evaluate AOI groups as a means of providing individualized support for activity re-engagement as part of recovery oriented mental health rehabilitation.